Effectivenessitas of Nutritional Management in Diabetes Mellitus Type II Nursing Care with Nutrition Deficit Nursing Problems - Rahmawati Shoufiah; Grace Carol Sipasulta (CV. Get Press Indonesia, 2025)
Type II Diabetes Mellitus is a chronic condition caused by impaired carbohydrate metabolism, which leads to insufficient insulin production. This study aims to assess the effectiveness of tailored nutritional interventions in improving the nutritional status and blood glucose control of patients. Using a descriptive design case study approach to explore the implementation of nutrition management in nursing care in type II diabetes mellitus patients with nutritional deficit problems. The study shows that that most respondents were between the ages of 51-60 years who were predominantly female indicating that lifestyle and hormonal factors may contribute to a higher risk of diabetes complications in women. Therefore, the importance of a comprehensive approach to nutrition management, tailored to the specific metabolic needs of patients, and underscores the important role of nurses in promoting integrated nutrition care.